PENGARUH SELF ESTEEM DAN SELF EFFICACY TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN KERJA SEBAGAI VARIABEL INTERVENING PADA KANTOR DINAS PENDIDIKAN SAWAHLUNTO - Alfindo Febrian; Ronni Andri Wijaya; Selvi Yona Sari (Management Studies and Business journal, 2024)
This research aims to determine and attempt to analyze the influence of self-esteem and self-efficacy on employee performance through work commitment as an intervening variable at the Sawahlunto Education Office. This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample of this research are employees of the Sawahlunto Education Office. The research results found that there is an influence between Self Esteem and Work Commitment. There is no influence between Self Efficacy and Work Commitment. There is no influence between Self Esteem on Employee Performance. There is no influence between Self Efficacy on Employee Performance. There is a relationship between Work Commitment and Employee Performance. Work Commitment mediates Self Esteem on Employee Performance. Work Commitment does not mediate Self Efficacy on Employee Performance.